ANALISIS SALURAN PEMASARAN DAN TRANSMISI HARGA KARET (Havea brasiliensis) PADA PETANI SWADAYA DI DESA PULAU JAMBU KECAMATAN KUOK KABUPATEN KAMPAR - Tanti Oktaria; Ermi Tety; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This reseacrh aim is to know and analyze: 1. The channel, margin of karet marketing and karet marketing efficiency. 2. The correlation between the price of karet from factory and the price of karet in farmer level. 3. The influence of karet price changing of factory to farmer level at Pulau Jambu Village of Kuok District of Kampar Regency. The reseacrh method is used of suervey method. The sampling method is purposive sampling of 40 farmers. And the second sampling of merchant is using snowball sampling method that come to marketing channel. The research result shows that in Pulau Jambu Village of Kuok District of Kampar Regency have one rubber marketing channel (homogeneity). That is farmer to collector merchant to factory. The lowest price in farmer level is Rp. 7.075/kg, and the highest price level is Rp. 11.450/kg. Then the lowest price of factory is Rp. 9.350/kg. And the highest price level of factory is Rp. 13.250/kg. The average price level of the farmer level on period Juli 2013 up to Juni 2014 is Rp. 9.096,53 and the average price level on factory is Rp. 11.267,57. The margin level of marketing channel between the price farmer level and factory is Rp. 2.171,04 and marketing eficiency is 4,49%. The correlation value between the price in farmer level and factory level is 0,95%. The value of the elasticity of price transmission between the price received from farmers and the price of karet by factory was 0,95%. Keywords : Marketing Channels, Marketing Margins, Price Transmission Elasticity, Rubber Farmers